Growth or Stagnation in the American Economy - Hansen, Alvin H. (The Review of Economics and Statistics, 1954)
M R. J. Steindl's book, Maturity and Stagnation in American Capitalism,' was completed in the summer of I949, prior to Korea. At that moment the United States was experiencing a recession and all the free world was worried lest it might develop into a serious depression. The outlook seemed to point toward the continuation of rather moderate military expenditures, and it was perhaps even possible to hope for a gradual approach to a more peaceful world. Since then we have had the shock of the Korean War and the enormous increase in military outlays 2 with the prospect of continued high levels of expenditure, not indeed at the peak levels, but at levels far beyond anything envisaged in I949. In the kind of world now in prospect, the problem of stagnation assumes a quite different aspect from that of I949. Indeed even in I949, with a federal budget of about $40 billion, half of which was for national security, the situation was obviously not at all like the peacetime conditions prevailing in the 'thirties before the Second World War. It is amazing how many economists have been able to close their eyes and blandly announce that events since I940 have disproved the stagnation thesis! Perhaps Mr. Steindl might concede that under current foreseeable conditions (despite some considerable decline in military expenditures) it makes no sense to talk about stagnation except in terms of past history. But I suspect that he might disagree. And, indeed, unless fairly drastic action is taken, there is a serious danger that we may move sidewise in the United States or even slip down gradually over the next few years. Measured against the attainable growth of GNP of which we are capable, such an experience would indeed be a form of stagnation. The mere maintenance of the GNP at the level of the second best year would give us ten to twelve million unemployed four years hence. It is therefore perhaps not altogether a useless exercise to reexamine, as Mr. Steindl does, the stagnation thesis. To begin with, it may be well to attempt a short classification of stagnation hypotheses, in order to give perspective to Mr. Steindl's thesis, as follows: i. A theory based primarily on exogenous.' factors including technology, population growth, and the opening up and development of new territory. This point of view is represented by my own analysis and perhaps also that of Harrod. 2. A theory based primarily on fundamental changes in social institutions, such as increasing state intervention in the form of the welfare state and related developments including the growth of the labor movement. This development, it is argued, has afflicted a formerly vigorous capitalism with a bad case of arterial sclerosis. This point of view is represented by Schumpeter in his Capitalism, Socialism and Democracy. 3. A theory based on endogenous factors inherent in the development of capitalism primarily the development of imperfect competition, monopoly, and oligopoly. This point of view is represented by Steindl in the book here under review. In his endogenous theory of stagnation, Mr. Steindl argues that already as early as the I890's the American economy had undergone a transition to the oligopolistic pattern. Stagnation did not come overnight. There had been going on a long process of secular change. Hardly anybody during the 'New Era' was aware of the fact that the annual rate of growth of business capital then was only half